ANALYSIS OF CROSS-SECTOR GOVERNANCE IN TOURISM INFRASTRUCTURE DEVELOPMENT IN CANGGU VILLAGE, BADUNG REGENCY - I Gusti Ngurah Anom Darsika; I Wayan Sudemen; Nyoman Sumawidayani (Jurnal Widya Publika, 2026)
The development of the Canggu Shortcut as an infrastructure solution faces not only technical challenges but also cross-sector governance issues involving various actors with different interests and authorities. This study aims to analyze cross-sector governance in tourism infrastructure development in Canggu Village, Badung Regency, particularly in the Canggu Shortcut project. The research employed a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving informants from government institutions, the private sector, and local communities. Data were analyzed using the interactive model developed by Miles and Huberman. The findings indicate that cross-sector governance in the development of the Canggu Shortcut has involved various stakeholders, including the Public Works and Spatial Planning Agency (PUPR), the Transportation Agency, the Regional Development Planning Agency (Bappeda), the Tourism Office, village governments, and private-sector actors. However, its implementation has not yet been fully optimal. Inter-agency coordination remains sectoral in nature, policy priorities differ among institutions, and program synchronization is still limited. Community participation remains largely consultative, while private-sector involvement has not been maximized. Transparency is primarily administrative, and comprehensive impact evaluation remains limited. Although the development project has contributed to improving accessibility, stronger and more integrated cross-sector governance is still required to support sustainable tourism development